2015
DOI: 10.1002/zaac.201400590
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Frustrated Double Perovskites: Synthesis, Structural Properties, and Magnetic Order of Sr2BOsO6 (B = Y, In, Sc)

Abstract: Abstract. Double perovskites Sr 2 BOsO 6 (B = Y, In, and Sc) were prepared from the respective binary metal oxides, and their structural, magnetic, and electronic properties were investigated. At room temperature all these compounds crystallize in the monoclinic space group P2 1 /n. They contain magnetic osmium (Os 5+ , t 2g 3 ) ions and are antiferromagnetic insulators with Néel temperatures T N = 53 K, 26 K, and 92 K for B = Y, In, and Sc, respectively. Powder neutron diffraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 49 publications
21
81
1
Order By: Relevance
“…This number is significantly reduced from the expectation of a magnetic ion with 3 unpaired electrons. However, the result is in excellent agreement with several recent neutron diffraction studies in Os 5+ bearing double perovskites [35,36] where the moment is found to be reduced primarily due to the effects of covalency in the Os−O bonds. While calculations indicate the Os moment is reduced primarily through covalency with oxygen, a small reduction due to spin-orbit coupling is also permitted [36,37].…”
Section: +supporting
confidence: 91%
“…This number is significantly reduced from the expectation of a magnetic ion with 3 unpaired electrons. However, the result is in excellent agreement with several recent neutron diffraction studies in Os 5+ bearing double perovskites [35,36] where the moment is found to be reduced primarily due to the effects of covalency in the Os−O bonds. While calculations indicate the Os moment is reduced primarily through covalency with oxygen, a small reduction due to spin-orbit coupling is also permitted [36,37].…”
Section: +supporting
confidence: 91%
“…In subsequent cycles the displacement parameters were refined while the occupancies were fixed. This procedure was repeated several times, while the scale factor, peak-shape parameters, asymmetry parameters, lattice [16][17][18][19][20][21][22]30], but they are lower than the theoretical spin-only moment (3.87 μ B ) for Os 5+ (S = 3/2), which can be partially attributed to the reduction of Os 5+  eff due to spin-orbit coupling. It has been suggested that the effect of spin-orbit coupling cannot be ignored in 4d 3 and 5d 3 systems [31].…”
Section: Methodsmentioning
confidence: 99%
“…Most of the well-studied double perovskites with nonmagnetic B cations and Os 5+ forming the B′ sublattice known so far display AFM transitions [16][17][18][19][20][21][22][23]. Because the magnetic interactions between the nearest-neighbor (NN) Os 5+ ions are usually thought to run mainly via the Os 5+ -O-O-Os 5+ path [16,17,20,22], the nonmagnetic B cations are not expected to play an important role in the magnetic exchange interactions. However, investigations on Sr 2 BOsO 6 (B = Sc, Y, In) indicate that the electronic configuration of the nonmagnetic B cation, d 0 or d 10 , does influence the magnetic exchange interactions [16,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is normally assumed to be fully orbitally quenched, resulting in a relatively classical S = 3/2 moment behavior [8]. However, many investigations in 4d 3 and 5d 3 compounds have found that the ordered magnetic moment measured by neutron diffraction is significantly reduced from the spin only value of µ = 3 µ B [3,[9][10][11][12][13][14]. Explanations of this reduced moment have centered on covalency and frustration.…”
mentioning
confidence: 99%